A Photoplethysmography Melanin Evaluation System by Modified Boltzmann Transport Equation (BTE). (22nd June 2015) - Huang, Sheng-Chieh; Wang, Hui-Min; Luo, Shi-Han
Abstract : With the advance in cosmetic medical technology in recent years, more and more people get cosmetic medical treatments, especially skin whitening treatments. Nevertheless, people usually assess the effect of skin whitening products by vision, which is subjective and will be different from each person. To acquire the value of melanin concentration objectively, people need to go to cosmetic medical clinics. This will cause inconvenience to people. This paper develops a novel evaluation platform based on optical assessment methods, which employ different absorption and scattering properties to different wavelengths of light in human tissue to obtain melanin concentration. Moreover, this paper proposes a new method that compensates the interaction between epidermis and dermis to acquire the melanin concentration more accurately. The novel platform designed in this paper is smaller and consumes lower-power and smaller when comparing to other conventional devices in market.